Análise sistemática dos aspectos ambientais do consumo de EPIs poliméricos durante a pandemia e ACV da produção de respiradores PFF2 sem válvula com polímero reciclado visando redução dos impactos ambientais. - Teixeira, Luiz Gustavo (Universidade Federal de São Carlos, 2024)
The increased consumption of Personal Protective Equipment (PPE) such as masks, face shields, glasses and gloves to combat the Covid-19 pandemic has increased the generation of polymeric waste. As production and consumption patterns in industry and society generate environmental impacts, studies focused on the increase in polymer consumption during and after the Covid-19 pandemic are essential. The general objective of this work was to propose actions to reduce the impacts generated by the production of FFP2 respirators without valves, considering the increase in consumption of these respirators during the Covid-19 pandemic. Through a systematic literature review (RBS), it was identified that the main environmental aspects linked to the increase in PPE consumption were: i) environmental pollution; ii) increase in microplastics in water; iii) water contamination; iv) food contamination; v) reduction/elimination, recycling in some locations; vi) increase in the consumption of virgin polymers. In the LCA, according to OpenLCA standard protocols, AGRIBALYSE_V301 database, ECOINVENT v3.7.1 database and ReCiPe 2016 Midpoint (H) calculation methodology, five scenarios were proposed with different proportions of secondary recycling polypropylene for the manufacture of the FFP2 respirator without valve, due to its higher consumption and similarity with the N95. Among the 18 impact category options, global warming and water consumption were presented in greater detail. The results indicate that the use of 10% recycled polypropylene might cause the lowest environmental impacts in terms of greenhouse gas (GHG) emissions and water consumption to generate electricity. In addition, it also has a potential to reduce the monthly consumption of fossil resources by around 97.87 t Oil eq and the emissions of toxic substances by around 90.60 t 1.4-DCB. This work also suggests future LCA studies using different scenarios, such as national polypropylene, rainwater, wind or solar energy, and recycled aluminum.
Systematic review of the environmental aspects of the consumption of polymeric PPEs during the pandemic and LCA of the production of the FFP2 valveless respirator with recycled polymer to reduce environmental impacts.
Keywords: ACV; Covid-19; EPI; Aspecto ambiental; Impacto Ambiental; PFF2; Polipropileno; PP; Resíduo; LCA; PPE; Environmental aspect; Environmental impact; FFP2; Polypropylene; Waste; CIENCIAS EXATAS E DA TERRA::QUIMICA; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO::DESENVOLVIMENTO DE PRODUTO; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA::ANALISE DE CUSTOS; ENGENHARIAS::ENGENHARIA DE PRODUCAO; ENGENHARIAS::ENGENHARIA QUIMICA; ENGENHARIAS; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::POLIMEROS